2021
DOI: 10.4103/iju.iju_414_20
|View full text |Cite
|
Sign up to set email alerts
|

The impact of transition from conventional robot-assisted radical prostatectomy to retzius sparing robot-assisted radical prostatectomy: A retrospective multivariate analysis

Abstract: Introduction: To assess the outcomes of Retzius sparing robotic-assisted radical prostatectomy (RS-RARP) in comparison with the conventional RARP. Materials and Methods: A retrospective analysis of 320 cases of RARP, performed from 2014 April to 2019 April, was performed. The predictor variables included age, body mass index, clinical stage, prostate-specific antigen, Gleason score category in biopsy, D'Amico risk category, presence of the median lobe, prior transurethr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…Kishore et al 12 realizaron un análisis retrospectivo para comparar la PRRA convencional vs. la PRRA-RS en 320 casos, evaluando entre sus variables la posiblidad de realizar el abordaje RS. Se excluyeron 23 pacientes, evaluando un total de 297.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Kishore et al 12 realizaron un análisis retrospectivo para comparar la PRRA convencional vs. la PRRA-RS en 320 casos, evaluando entre sus variables la posiblidad de realizar el abordaje RS. Se excluyeron 23 pacientes, evaluando un total de 297.…”
Section: Resultsunclassified
“…Los márgenes quirúrgicos positivos después de PRRA-RS y PRRA convencional fueron del 29.9% y el 33.0%, respectivamente, con un incremento en la zona posterolateral, anterior y apical de la próstata, siendo más frecuente en pacientes con pT3. La recurrencia bioquímica posterior al año fue del 31% para PRRA convencional y del 21% para PRRA-RS; subsecuentemente, el 29.9% recibieron hormonoterapia y el 18.8% radioterapia en el grupo de PRRA convencional, mientras que en el de PRRA-RS el 26% recibieron hormonoterapia y el 11% radioterapia 12 . Karsiyakali et al 13 incluyeron 238 pacientes para comparar la PRRA convencional vs. la PRRA-RS.…”
Section: Resultsunclassified
“…Of note, 24 studies comparing RS-RARP to other approaches have been published up to April 15, 2023. Most reports aimed to demonstrate differences between RS-RARP and other approaches in terms of early and late urinary continence (Table 1) [5–8,9 ▪ ,10,11 ▪ ,12–16,17 ▪ ,18,19 ▪ ,20–22,23 ▪ ,24 ▪▪ ,25–28], but none focused on erectile function as primary endpoint. A minority of the studies reported data on sexual function, never finding significant differences among the RARP approaches.…”
Section: Literature Overviewmentioning
confidence: 99%
“…Работа в операционном поле и визуальные преимущества РАРП изначально были восприняты с энтузиазмом, так как было много положительных отзывов от хирургов, выполняющих оперативные вмешательства на роботе Da Vinci. Различные исследования продемонстрировали раннее восстановление континенции (<90 дней) после РАРП при выполнении тщательного рассечения верхушки, передней и задней реконструкции и сохранении шейки мочевого пузыря [19]. Однако проспективное исследование, анализирующее 12-месячную континенцию во всех категориях риска, выявило аналогичные результаты между РАРП и открытой РПЭ (OR: 1.08; 95 % доверительный интервал ДИ 0,87-1,34) [1].…”
Section: анализ функциональных результатовunclassified